(untitled) (EU and comparative law issues and challenges series (ECLIC), 2021)
Bosnia and Herzegovina, having an extremely complex state system and at the same time being a developing country and economy in transition with a commitment to membership in the European Union, faces numerous challenges in adapting national legislation to the acquis communautaire. One of the key segments of the introduction of European standards is the establishment of an effective mechanism for the protection of competition in legislative and institutional terms. With the adoption of the Competition Law in 2005, which brings new solutions and is largely in line with the acquis, Bosnia and Herzegovina has made a significant step forward from the previous state of legal irregularity in this important segment. However, sixteen years of the enforcement of the BiH Competition Law have shown certain shortcomings regarding the particular solutions contained in it. These shortcomings concern the part of the provision of the law that regulates procedural issues, but also the functioning of the authority responsible for the protection of competition in Bosnia and Herzegovina and it can be assumed that these are obstructive elements in response to the challenges of COVID-19 pandemic. In order to follow the international trends, companies in BiH have entered into a process of business digitalization, which, however, being accelerated due to COVID-19 pandemic, has created many challenges before the Council of Competition of BiH as the authority responsible for public enforcement of the competition law. The aim of this paper is to question the extent to which COVID-19 pandemic has affected the work of the Council of Competition BiH, as well as to address some of the particular issues it has faced before the pandemic, including growing market concentration, growing power of digital platforms, protectionism, consumer vulnerability and consequent loss of public confidence. In order to meet the set research goals, the first part of the paper will present an analysis of the legal solutions in the context of the legal and institutional aspect of competition protection and will provide an overview of the situation regarding the digitalization of business operations in Bosnia and Herzegovina. The second part of the paper will provide an analysis of the work of the Council of Competition of BiH with special reference to the period of declaring the pandemic COVID-19.